Digitalization of Local Cultural Arts as an Innovation in Arts Education in the Era of Merdeka Belajar - Sahnir, Nurachmy; Jamilah, Jamilah; Yatim, Heriyati (Universitas Negeri Makassar, 2025)
The digital transformation in education offers a significant opportunity to revitalize local cultural arts through innovative learning approaches. However, the integration of local cultural arts into digital educational media particularly in school-based arts education remains suboptimal. This study aims to explore the potential of local cultural arts digitalization as a form of innovation in arts education aligned with the Merdeka Belajar policy. This research adopts a qualitative approach, utilizing interviews, observations, and documentation studies involving arts teachers, students, and local cultural content in elementary school settings. Findings indicate that using digital media rooted in local culture such as traditional dance videos, interactive applications, and folklore animations can increase student interest and strengthen cultural identity. The conclusion affirms that the digitalization of local cultural arts is effective not only as a medium for arts education but also as a strategy for cultural preservation that is adaptive to the digital era and education policies grounded in local wisdom.